1952
DOI: 10.1002/j.2333-8504.1952.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Experimental Level of Aspiration Techniques for Group Administration*

Abstract: The purpose of this research was to determine whether it was feasible to develop group‐testing techniques suitable for obtaining experimental level of aspiration measures. Incorporating a number of desired characteristics which grew out of a review of the literature, three experimental level of aspiration techniques were developed and investigated empirically. These techniques yielded reliable derived aspiration scores possessing satisfactory distribution characteristics. Instructions asking for levels of aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1952
1952
1954
1954

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Both types of' instructions have been used in previous studies (3,7,8) and have been shown to produce different effects. The authors (9) found neither type to result in more reliable or more generalized scores, although the "Goal" type produced higher average goal discrepanoy scores arid greate~soore dispersion.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Both types of' instructions have been used in previous studies (3,7,8) and have been shown to produce different effects. The authors (9) found neither type to result in more reliable or more generalized scores, although the "Goal" type produced higher average goal discrepanoy scores arid greate~soore dispersion.…”
Section: Methodsmentioning
confidence: 93%
“…In most of the previous experimental level of aspiration studies individual testing procedures have been employed because of the complicated nature of the testing techniques required and because motor tasks were frequently utilized. In another paper (9) the writers have described the development of three experimental level of aspiration techniques suitable for group administration. Various tasks are included in these techniques but, in each case, several trials of the task are given, the subjects scoring their own performance after each trial and.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Retationship between Group Experimental Level of Aspiration ~2-group ailm1 nj stration (10). These group techniques were intended to parallel the classical individually a¢ministered level of aspiration methods, and were developed after a survey had.been made of the many methodological variations which are found in level of aspiration studies (9).…”
Section: Introductionmentioning
confidence: 99%